Kedudukan Direktorat Jenderal Hak Kekayaan Intelektual (HKI) dalam Perlindungan Hak Cipta Lagu - Yoaneta Spiridiana Sorowea; I Nyoman Sukandia; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2024)
Copyright is the exclusive right of creators to regulate the ownership and distribution of their work. In Indonesia, the Directorate General of Intellectual Property Rights (IPR) plays a role in ensuring that copyright is protected and enforced, including in the context of music or songs. The focus of this research is to evaluate how the law, specifically Law Number 28 of 2014 on Copyright, provides legal protection to songs. In addition, the research also examines the role of the Directorate General of Intellectual Property in providing protection to song copyrights. The research method used is the normative method. The results showed that in the case of the song "Gemu fa mi re", the creator has the right to file a lawsuit to the court in case of piracy or unauthorized duplication. Preventive efforts are made by registering copyrighted works with the authorized institution, while repressive efforts involve filing a lawsuit in court in cases of copyright infringement. In the context of the position of the Directorate General of Intellectual Property, they have an important role in providing legal protection to copyrighted works. This involves policy implementation, provision of technical guidance, supervision, evaluation, and reporting in various aspects, such as applications, publications, legal services of copyright, products, and related rights.